Olschewian and appearance of bone technology in Croatia and Slovenia - Karavanić, Ivor (Array, 1999)
Early Upper Paleolithic of northwestern Croatia and Slovenia is characterized by an industry, usually described as Aurignacian, which contains Upper Paleolithic split-base and massive base (Mladeč) bone points and significant amount of typical Mousterian stone tools (sidescrapers, denticulated pieces), together with some Upper Paleolithic stone tools. This industry appears in period between 36ka and 32ka at Croatian sites of Vindija (level G1) and Velika Pećina (level i) and Slovenian site of Divje Babe I (layer 2), according to available radiocarbon dates. Probably around the same time or somewhat later it also appears at Slovenian sites of Potočka Zijalka and Mokriška Jama. Compared to the other mentioned sites, the archaeological assemblage of Potočka Zijalka contains larger number of bone points and stone tools that beside Mousterian types include a number of Aurignacian types (carinated and nosed endscrapers). At first J. Bayer named the industry of Potočka Zijalka as Olschewian. This designation was abandoned by M. Brodar and this industry was included in Aurignacian, but recently the term Olschewian has been resurrected by A. Montet-White. It is quite possible that archaeological assemblages from Vindija level G1, Velika Pećina level i, Divje Babe I layer 2 and Mokriška Jama, represent an Early Upper Paleolithic regional industry that has roots in local Mousterian stone technology and does not conform to classical Aurignacian pattern, even with its developed technology of making bone points (split and massive base). It also seems that Potočka Zijalka is closely related to the mentioned sites, but this site, as well as Vindija lower F complex levels, displays some affinity with Aurignacian in a broad sense. While lithic industry in all of these sites is closely related to Mousterian, their bone assemblage is entirely Upper Paleolithic, with exception of the bear baculum bone with carved circular markings which may have come from Vindija Mousterian level G3. The term Olschewian could be used to designate the initial industry of the Early Upper Paleolithic at northwestern Croatian and Slovenian sites, which in many ways displays a unique regional character and marks the first appearance of bone technology in these regions.